2002
DOI: 10.1016/s0960-9822(02)00930-2
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Protection by the Epo Target Bcl-XL Allows Factor-Independent Differentiation of Primary Erythroblasts

Abstract: During erythroid maturation, Epo regulates red cell numbers via apoptosis inhibition, caused by Epo-dependent upregulation of the antiapoptotic protein Bcl-X(L). This allows "default" terminal differentiation of apoptosis-protected, committed erythroblasts, independent of any exogenous signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 40 publications
4
121
0
Order By: Relevance
“…29 Signaling from EpoR through Jak2/Stat5 30,31 prevents apoptosis on this cell lineage from late erythroid progenitors (CFU-E) until the onset of hemoglobinization, 32,33 and one important target gene of this cascade is bcl-x. 34 Studies using bcl-x-null mice demonstrated a critical role for this gene at the end of erythroid maturation when maximal hemoglobin synthesis occurs. 35 RBPjk À/À erythroid cells show a clear upregulation of genes involved in this antiapoptotic pathway, such as EPO, EPO-R, bcl-x and bcl-2, suggesting that Notch may induce apoptosis by impinging on this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…29 Signaling from EpoR through Jak2/Stat5 30,31 prevents apoptosis on this cell lineage from late erythroid progenitors (CFU-E) until the onset of hemoglobinization, 32,33 and one important target gene of this cascade is bcl-x. 34 Studies using bcl-x-null mice demonstrated a critical role for this gene at the end of erythroid maturation when maximal hemoglobin synthesis occurs. 35 RBPjk À/À erythroid cells show a clear upregulation of genes involved in this antiapoptotic pathway, such as EPO, EPO-R, bcl-x and bcl-2, suggesting that Notch may induce apoptosis by impinging on this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…34 Studies on an immortal line of phenotypically normal mouse erythroblasts provided further details about the antiapoptotic role of Bcl-X L in erythroid maturation. 35 These cells were maintained in an undifferentiated state by agents promoting selfrenewal, such as SCF and glucocorticoids, while they were induced to differentiate by Epo. Overexpression of the Bcl-X L gene allowed these cells to undergo terminal differentiation to mature erythrocytes in the absence of Epo.…”
Section: Figurementioning
confidence: 99%
“…Overexpression of the Bcl-X L gene allowed these cells to undergo terminal differentiation to mature erythrocytes in the absence of Epo. 35 The molecular basis responsible for the elevated expression of Bcl-X L in erythroid cells is unknown at the moment. The promoter of the Bcl-X L gene used for the start of the transcription in erythroid cells is localized at 5 0 in close proximity to the start initiation codon ATG.…”
Section: Figurementioning
confidence: 99%
“…In the past several years in vitro culture systems have been developed that faithfully recapitulate red blood cell development in vitro employing various types of hematopoietic progenitor cells and culture conditions (Fibach et al, 1991;Dolznig et al, 1995Dolznig et al, , 2001Dolznig et al, , 2002Wessely et al, 1997;Bartunek and Zenke, 1998;Panzenbock et al, 1998;von Lindern et al, 1999;Zhang et al, 2001;Bartunek et al, 2002). Such in vitro differentiation systems have allowed the study of the molecular mechanisms that underlie the erythroid cell differentiation program.…”
Section: Introductionmentioning
confidence: 99%